The United Kingdom's Human Rights Act as a Catalyst of Constitutional Migration: Patterns and Limitations of Rights Importation by Design. (March 2023) - Masterman, Roger
Abstract : The United Kingdom Human Rights Act 1998 – Constitutional migration – Impacts of legislative design and process on the internalisation of international standards – A taxonomy of migratory patterns under the Human Rights Act – Constitutional migration as a source of constitutional instability – Proposals for a British Bill of Rights